Kesiapan Menikah dalam Perspektif Psikologi Pendidikan Agama Islam - Munzillah, Indiarti Muafiqoh; Azkiyah, Azkiyah; Rohimah, Siti (Lembaga Yasin AlSys, 2024)
Marriage is one of the important stages in a person's life according to Islamic teachings. In the context of educational psychology, marriage readiness involves psychological aspects such as emotional maturity, mental stability, independence, and an understanding of roles and responsibilities as a husband or wife. From the point of view of Islam, readiness for marriage also includes an understanding of spiritual values, religious responsibilities, and readiness to foster a harmonious household based on Islamic teachings. By understanding this perspective, it can help individuals in making the right decisions and preparing themselves well before entering the marriage bond. This study aims to determine the readiness to get married from the perspective of Islamic religious education psychology and to find out the factors of readiness for marriage. The research method carried out is using qualitative research methods with a literature model. The stages in analysing data are doing it by reducing data, presenting data, and drawing conclusions. The researcher reduces the literature on marriage readiness from the perspective of Islamic religious education psychology, then presents it systematically. The final stage is to draw conclusions from critical analysis. The result of this study is Don't get married just because you're in love. Marry because you believe that the paradise of Allah Almighty is nearer with him. Getting married is the longest worship, make sure you have the knowledge to carry it out. Getting married is easy, it's just that the mind complicates it because of the fears in marriage, especially in financial matters. Meanwhile, the factors that need to be prepared for moral, spiritual, physical, psychological and, material maturity.